Vanillin derivative as performing type I photoinitiator. (5th June 2020) - Breloy, L.; Negrell, C.; Mora, A.-S.; Li, W. S. Jennifer; Brezová, V.; Caillol, S.; Versace, D.-L.
Graphical abstract: Highlights: Vanillin can be used as a scaffold for the synthesis of type I photoinitiator. Vanillin-derived type I photoinitiator generates highly reactive radical species. Vanillin-derived photoinitiator induces free-radical photopolymerization. Abstract: A new efficient type I photoinitiator derived from vanillin was synthesized to initiate, according to a green photoinduced process, the free-radical polymerization (FRP) of acrylate monomers in a reduced time and under air. Interestingly, this unprecedented photoinitiator lead to high acrylate conversions even under air, with a higher efficiency than some reference photoinitiating systems commonly used in FRP.